PENDAMPINGAN PENGOLAHAN KOTORAN SAPI MENJADI PUPUK ORGANIK - Hodi Eko Prasetio; Muhammad Dhurofallathoif; Tis’atun Nujum; Siti Inggil Puspa Jelita; Miskhatur Rofi’ah; Rofiatun Nisa' (Mafaza : Jurnal Pengabdian Masyarakat, 2023)
Behind its disgusting shape, cow dung has many ingredients that are very beneficial for soil fertility. This service was carried out in Slaharwotan Village, Ngimbang District, Lamongan Regency. In this village, the majority of people raise cattle, but the manure is wasted and not utilized. For this reason, this service aims to provide assistance to the cattle farming community to process wasted cow manure waste into organic fertilizer that can be used for agricultural soil fertility. This service method uses Participatory Action Research (PAR) with planning, implementation, and evaluation steps. Retrieval of community needs data by means of interviews and Focus Group Discussion (FGD). Assistance in making organic fertilizer is carried out in a simple way with additional ingredients in the form of EM4 and calcium. This activity is also an additional knowledge for farmers who do not understand how to make organic fertilizer properly. With this mentoring activity, the community knows that cow dung has beneficial value and can immediately practice independently in processing cow dung into organic fertilizer.